Genotyping serotonin transporter polymorphisms 5-HTTLPR and rs25531 in European- and African-American subjects from the National Institute of Mental Health’s Collaborative Center for Genomic Studies - Odgerel, Z; Talati, A; Hamilton, S P; Levinson, D F; Weissman, M M (Translational psychiatry, 2013)
A number of studies have suggested DNA sequence variability in the serotonin transporter gene ( SLC6A4 ) between European-American (EA) and African-American (AA) populations, which could be clinically important, given the central role SLC6A4 has in serotonin transmission. However, these studies have had relatively small samples, used self-reported measures of race, and have only tested the promoter-linked polymorphism 5-HTTLPR. Here we genotype 5-HTTLPR and rs25531, a neighboring functional polymorphism, in 954 AA and 2622EA subjects from a National Institute of Mental Health repository sample. Genotyping was performed using fragment analysis by capillary electrophoresis. AA, as compared with EA, groups had lower frequencies of the S allele (0.25 vs 0.43) and SS genotype (0.06 vs 0.19) at 5-HTTLPR, and higher rates of the G allele at rs25531 (0.21 vs 0.075). A rare xL variant at 5-HTTLPR was also more common among AAs (0.017 vs 0.008). When the polymorphisms were redefined into a high- and low-transcription haplotypes, the AA group showed significantly fewer low-transcription variants ( χ 2 =4.8, P =0.03). No genotypes were associated with major depression, any anxiety disorder, or neuroticism in either EA or AA populations. This is the largest study to show SLC6A4 genotype differences between EA and AA populations, and the first to include rs25531. Lack of associations with clinical outcomes may reflect untested moderating environmental influences.